Comparative study of greenhouse gas emission calculations and the environmental impact in the life cycle assessment of buildings in China, Finland, and the United States. (1st July 2023) - Shi, Ligang; Qi, Xinzhu; Yang, Zhaojing; Tao, Lulu; Li, Yuqing; Qiu, Jinghan; Jiang, Xintong
Abstract: The building sector is considered a leading contributor to global greenhouse gas (GHG) emissions. With the implementation of China's 2030 carbon peak and 2060 carbon-neutral strategy, significant quantitative research regarding low-carbon buildings is crucial. However, a considerable discrepancy remains between the low-carbon building development in China and other advanced countries; the calculation method of GHG emissions lacks international integration. Based on the life cycle assessment (LCA) theory, a comparative empirical analysis was conducted among residential and public building sets in China, Finland, and the United States considering the life-cycle GHG emissions, which demonstrated notable differences in the Product stage (A1–A3), Maintenance and material replacement stage (B1–B5), and Energy use stage (B6) between each building set. Different building retrofit scenarios were then established to study the emission reduction methods. The results suggest that clean energy sources, materials with low global warming potential, engineered wood structures, and steel structural beams in long-span buildings are conducive to reducing GHG emissions throughout the life-cycle of buildings. Highlights: Global warming potentials of typical residential and public buildings were analysed. GHG emissions of cases from China, Finland, and the United States were calculated. Scenarios were set up to explore the method of reducing Greenhouse gas emissions. Substituting concrete products with wood and steel reduces environmental impact.